Why isn’t FAIR enough? Bringing together methods and values for Open Science uptake - Di Donato, Francesca; Provost, Lottie (Umanistica Digitale, 2025)
The FAIR principles have emerged as a global standard for Research Data Management but their application has not had the expected impact, especially considering the considerable amount of funding which has been put into FAIR policies. In fact, open research methods have not become the norm, FAIR is still perceived as just another mechanical task for researchers, and quality is still not ensured by the application of the principles. The CARE principles were proposed to complement the FAIR framework, arguing that people and purpose, rather than data and technology, should be at the centre of RDM frameworks. In practice, they have been applied in certain contexts, which we will examine, but their impact has been rather limited. In this article, we will therefore analyse the definition of the Open Science values and principles provided in the UNESCO Recommendation. By doing so, we aim to see if they overlap with the CARE values and principles, and to understand if the latter are useful, and for what. Finally, we note that the UNESCO definition of Open Science already encompasses the values and principles of CARE, while also being broader and more comprehensive. The implementation and practical translation of the FAIR principles into research practices must address an underlying cultural challenge, and this is where the CARE principles can provide meaningful insight, emphasising the importance of starting with context, communities, and their genuine needs. However, these principles are not indispensable, as these considerations are already embedded within the UNESCO Recommendation and, by extension, within the definition of Open Science itself—an ecosystem of practices in which Research Data Management is a foundational pillar.